Еконофізичні підходи до визначення обсягу інвестицій з урахуванням ступеня політичного ризику - Вітлінський, В.В.; Маханець, О.М.; Маханець, Л.Л. (Культура народов Причерноморья, 2013)
У роботі проаналізовано можливість використання понять еконофізики для моделювання
обсягів прямих іноземних інвестицій в економіку України з урахуванням ступеня політичного ризику та
зовнішнього боргу. Доведено можливість використання законів ідеального газу для аналізу економічних
систем, а саме, для оцінювання ступеня політичного ризику за сталого обсягу зовнішнього боргу.
Побудовано ізокванти зовнішнього боргу, які дозволяють дослідити перехід економічної системи з
одного стану в інший за сталого обсягу зовнішнього боргу В работе проанализирована возможность использования понятий эконофизики для
моделирования объемов прямых иностранных инвестиций в экономику Украины с учетом степени
политического риска и внешнего долга. Доказана возможность использования законов идеального газа
для анализа экономических систем, а именно, для оценки степени политического риска. Построены
изокванты внешнего долга, которые позволяют исследовать переход экономической системы из одного
состояния в другое при постоянном объеме внешнего долга. The using of econophysics' concepts for modeling foreign direct investment in Ukraine, taking into
account the degree of political risk and foreign debt is analyzed in the paper. It is shown that the degree of
political risk and the amount of investments act as an indicator of stability in the country. The possibility of
using the ideal gas law for the analysis of economic systems, especial for assessing the degree of political risk
for the sustainable amount of debt is shown. Also it is shown that the economy as a system and the concept of an
ideal gas have identical parameters. The econometric model depending foreign direct investment from political
risk and foreign debt constructs in the paper. The isoquant of external debt, which allow to investigate the
transition of the economic system from one state to another for a sustainable amount of debt and characterize
the stability and resilience of the economy is built. The possibility of determining the required amount of foreign
direct investment, which would provide the optimal amount of debt and the degree of political risk, using
concepts econophysics is demonstrated in the paper. It is shown that using of ideal gas theory's concepts for the
analysis and evaluation of the degree of political risk can help determine reasonable (acceptable) amounts of
external debt and foreign direct investment for a certain level of country's political risk.